Compounds and Methods to Study O-GlcNAc Modification of Proteins - Zheng, Hongchao (My University, 2007)
A variety of important cell functions rely on O-GlcNAcylation of proteins, a kind of post-translational glycosylation that modifies nuclear and cytoplasmic proteins on serine or threonine residues by the addition of the single sugar moiety β-N-acetylglucosamine (O-GlcNAc). Generally, two enzymes can catalyze the formation and cleavage of the O-GlcNAc O-glycosidic linkage. The O-GlcNAc transferase (OGT) catalyzes the transfer of N-acetylglucosamine from uridine diphosphate N-acetylglucosamine to the hydroxyl group of specific Thr and Ser residues. On the other hand, hydrolysis of the sugar moiety from proteins is achieved via the bi-functional nuclear cytoplasmic O-GlcNAcase and acetyltransferase (NCOAT). Since O-GlcNAcylation plays very important roles in many cell processes such as transcription, translation and protein-protein interaction, my research mainly focused on preparing compounds and developing methods to study the O-GlcNAcylation process and discover the structural information of OGT and NCOAT.
In this thesis, the important enzyme substrates (YSDSPSTST for OGT and YSDSP(O-GlcNAc-Ser)TST for NCOAT) were prepared by solid phase synthesis and purified by preparative reverse phase HPLC. Their structure and sequence were confirmed by ESI-MS and tandem MS (MS/MS). The building block S-GlcNAc-Ac3-Ser-COOBn for preparing S-GlcNAcylated peptides was prepared by a multistep procedure. Two potent photoaffinity labeled probes for mapping the active site of sOGT were designed and synthesized, and their IC50 values for sOGT were measured by CapLC and a beta-elimination method. Also, many analytical methods were developed for studying the O-glcNAcylation, including discovering the O-Glycosylation site of peptides by MS/MS and beta-elimination methods, sequencing peptides by MS/MS, analyzing the protein digests by CapLC-MALDI MS and studying the ion mobility of peptides and glycopeptides using ion mobility spectrometry.
Keywords: compounds, methods, modification of proteins, cytoplasmic, glycosylation, hydrolysis, peptides